Pengaruh Likuiditas dan Solvabilitas terhadap Nilai Perusahaan Sub Sektor Food and Bevarage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Karisma, Adi; Purwanto, Tinggal; Kusumadewi, Ratna (JYRS: Journal of Youth Research and Studies, 2025)
The value of a company reflects investors' perceptions of the firm's condition, particularly in relation to its stock price. A high stock price indicates a high company value. Companies with high firm value tend to enhance investor confidence in the company's financial performance and managerial capabilities. Financial performance in this study is measured using liquidity, proxied by the Current Ratio (CR), and solvency, proxied by the Debt to Asset Ratio (DAR). The object of this research is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. This is a quantitative study that utilizes secondary data, with a purposive sampling technique. The study population consists of 95 companies, with a final sample of 8 companies. The analytical methods employed include descriptive statistical analysis, panel data regression, classical assumption tests, and hypothesis testing. Data were processed using EViews 9 software. The results of the study show that, partially, the Current Ratio (CR) has no significant effect on firm value, with a probability value of 0.1672 > 0.05. Meanwhile, the Debt to Asset Ratio (DAR) has a negative effect on firm value, with a probability value of 0.0008 < 0.05. Simultaneously, both the Current Ratio (CR) and the Debt to Asset Ratio (DAR) have a significant effect on firm value, with a probability (F-statistic) of 0.002635 < 0.05.